Long COVID in Children and Adolescents: A Critical Review - Maria Rothensteiner; Franziska Leeb; Florian Götzinger; Marc Tebruegge; Angela Zacharasiewicz (MDPI AG, 2024)
(1) Background: Data on persisting symptoms after SARS-CoV-2 infection in children and adolescents are conflicting. Due to the absence of a clear pathophysiological correlate and a definitive diagnostic test, the diagnosis of Long COVID currently rests on consensus definitions only. This review aims to summarise the evidence regarding Long COVID in children and adolescents, incorporating the latest studies on this topic. (2) Methods: We designed a comprehensive search strategy to capture all relevant publications using Medline via the PubMed interface, with the initial literature search conducted in April 2023. To be included, publications had to present original data and include >50 participants with Long COVID symptoms aged between 0 and18 years. (3) Results: A total of 51 studies met the inclusion criteria, with most studies originating from Europe (n = 34; 66.7%), followed by the Americas (n = 8; 15.7%) and Asia (n = 7; 13.7%). Various study designs were employed, including retrospective, cross-sectional, prospective, or ambispective approaches. Study sizes varied significantly, with 18/51 studies having fewer than 500 participants. Many studies had methodological limitations: 23/51 (45.1%) studies did not include a control group without prior COVID-19 infection. Additionally, a considerable number of papers (33/51; 64.7%) did not include a clear definition of Long COVID. Other limitations included the lack of PCR- or serology-based confirmation of SARS-CoV-2 infection in the study group. Across different studies, there was high variability in the reported prevalence of Long COVID symptoms, ranging from 0.3% to 66.5%, with the majority of studies included in this review reporting prevalences of approximately 10-30%. Notably, the two studies with the highest prevalences also reported very high prevalences of Long COVID symptoms in the control group. There was a relatively consistent trend for Long COVID prevalence to decline substantially over time. The prevalence of Long COVID appeared to differ across different paediatric age groups, with teenagers being more commonly affected than younger children. Furthermore, data suggest that children and adolescents are less commonly affected by Long COVID compared to adults. In children and adolescents, Long COVID is associated with a very broad range of symptoms and signs affecting almost every organ system, with the respiratory, cardiovascular, and neuropsychiatric systems being most commonly affected. (4) Conclusions: The heterogeneity and limitations of published studies on Long COVID in children and adolescents complicate the interpretation of the existing data. Future studies should be rigorously designed to address unanswered questions regarding this complex disease.